Studying literature : An introduction to fiction and poetry - Pramdod K Nayar; Nayar, Pramod K (Hyderabad Orient Blackswan, 2019)
studying literature is a short introduction to two genres in literary studies: fiction and poetry. It explicates in easy-to-understand terms the basic elements of a fictional work, such as plot, setting, Characterisation and point of view; and the constituents of a poem, such as tone, diction, imagery and figurative language. Each of these elements is explained through the analysis of examples from assorted literary texts from around the world. The explanations are supplemented with examples from films, celebrity culture and political speeches. The book offers a point of departure for students embarking on literary studies. It foregrounds the literariness and special use of the language of poetry and fiction, and demonstrates how these texts are put together
Keywords: Indian English Miscellaneous; Indian English Literature